(3TQM efXheI GHf hgHGfs - (3CHh GdHQcGJ, GHf GdTMfI, SQj GdOjf, YHO GdHQ Hf eMeO Hf eMeO, J (B921 (3g`s ((3YHO GdQMef Hf GdYeGO GdZRhdj GdfGSNs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3aUd ef cJGH GdhcGdI , GdhcGdI HaJM GdhGh hcSQgG GSe ddJhcd ef hcdJc HcPG EPG ahVJg Edjc hajg GXgGQ GdYLQ hGdGYJeGO Ydi GdZjQ hTQYs
(3BNQgG (B:s
... (3hjTJQW chfg MQG PcQG ecdaG hGdJbhi TQW GdceGd adG jfYRd HGdaSb hdG jTJQW chfg gGTejG Hd chfg bQTjG hdG YUeJg bGOQG Ydi JfajP GdCMcGe hJfajP MOhO GdGSdGe hGddg JYGdi CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\273s
(3cTa GdXfhf (B2\1865s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis